Arabidopsis Endoplasmic Reticulum-Localized UBAC2 Proteins Interact with PAMP-INDUCED COILED-COIL to Regulate Pathogen-Induced Callose Deposition and Plant Immunity. Issue 1 (9th January 2019) - Wang, Zhe; Li, Xifeng; Wang, Xiaoting; Liu, Nana; Xu, Binjie; Peng, Qi; Guo, Zhifu; Fan, Baofang; Zhu, Cheng; Chen, Zhixiang
Abstract : The interacting ER proteins UBAC2 and PICC positively regulate the accumulation of the PMR4 callose synthase responsible for pathogen-induced callose deposition during plant immune responses. Abstract: Pathogen-associated molecular pattern (PAMP)-triggered immunity (PTI) is initiated upon PAMP recognition by pattern recognition receptors (PRR). PTI signals are transmitted through activation of mitogen-activated protein kinases (MAPKs), inducing signaling and defense processes such as reactive oxygen species (ROS) production and callose deposition. Here, we examine mutants for two Arabidopsis thaliana genes encoding homologs of UBIQUITIN-ASSOCIATED DOMAIN-CONTAINING PROTEIN 2 (UBAC2), a conserved endoplasmic reticulum (ER) protein implicated in ER protein quality control. The ubac2 mutants were hypersusceptible to a type III secretion-deficient strain of the bacterial pathogen Pseudomonas syringae, indicating a PTI defect. The ubac2 mutants showed normal PRR biogenesis, MAPK activation, ROS burst, and PTI-associated gene expression. Pathogen- and PAMP-induced callose deposition, however, was compromised in ubac2 mutants. UBAC2 proteins interact with the plant-specific long coiled-coil protein PAMP-INDUCED COILED COIL (PICC), and picc mutants were compromised in callose deposition and PTI. Compromised callose deposition in the ubac2 and picc mutants was associated with reduced accumulation of the POWDERY MILDEW RESISTANT 4 (PMR4) callose synthase, which is responsible for pathogen-induced callose synthesis. Constitutive overexpression of PMR4 restored pathogen-induced callose synthesis and PTI in the ubac2 and picc mutants. These results uncover an ER pathway involving the conserved UBAC2 and plant-specific PICC proteins that specifically regulate pathogen-induced callose deposition in plant innate immunity.